3D CAD method for smart garments fit prediction - Boldt, Rachel (2019)
In the scope of textile products categorized as "smart wearables," the perfect fit to the user's body is of central importance. The adjustment provides means for the full operation of the electronic system integrated with clothing. The main objective of this paper is to present the methodological path that constituted the redesign of the flat patterns of a smart t-shirt for vital monitoring, by comparing the process and benefits between a traditional method and 3d-2d Cad process to build the basic pattern blocks